Peer attachment as a protective factor against adolescent aggressiveness: Evidence from PLS-SEM analysis - Hinggardipta, Ratnasari; Fitri, Susi; Wahyuni, Eka; Paradhiba, Meutia; Siahaan, Perry Boy Chandra; Rimonda, Rubi (Universitas Islam Negeri Raden Intan Lampung, 2025)
The research focused on studying peer attachment and aggression among adolescents in South Tangerang. Data was collected from 320 adolescents aged 13-17 and included in the research study. Data were collected using the Peer Attachment Scale and the Aggression Questionnaire, which were adapted for the Indonesian environment and subsequently validated. The data were analyzed using SmartPLS 4, which applies Partial Least Squares Structural Equation Modeling (PLS-SEM). The research found evidence of a negative correlation, indicating that lower peer attachment was associated with higher levels of aggression (β = -0.503; f² = 0.21; Q² = 0.31). The most dominant influence on the ‘communication’ aspect of attachment was the most hidden form of aggression - ‘hostility.’ The structural pathways showed no significant variation based on the sex of the participants, indicating that strong correlates with peer attachment will result in less aggression in both females and males. The research discusses the most practical aspects of implementing CASEL’s social-emotional learning (SEL) modules, which focus on peer mentoring and support, as well as other school-based attachment programs, as detailed by the Australian Institute of Family Studies. Future research might include longitudinal study designs and explore mediation analyses on the relationships between the regulation of emotions and moral disengagement, as a means to clarify the connections within these relationships.